THE ROLE OF SELF EFFICACY TOWARD STUDENTS’ ACADEMIC CHEATING BEHAVIOR - Darmiany Darmiany; Iva Nurmawanti (Erudio Journal of Educational Innovation, 2020)
The purpose of this research is to determine the role of self-efficacy toward student academic cheating behavior. Primary School Teacher educate by mapping the types of fraud committed by students and to determine the the role of self-efficacy on the practice of cheating. To achieve these objectives the research was carried out with descriptive method. The data collection techniques used two instruments, they are the self-efficacy scale (SE) and the academic cheating (AC) scale toward 115 Undergraduate students of PGSD and Sociology Study Program Academic Year 2017-2018 FKIP University of Mataram. The results of the analysis using simple linear regression indicate that there is a role for self-efficacy to predict student academic cheating behavior with a value of F = 4.560 and a significance of 0.05 (p <0.05). There is a negative effect of Self Efficacy on student academic cheating behavior, the higher the self efficacy, the lower the level of academic cheating.